Modelling and analysis of rooftop PV as an energy optimization of flat roof and gable roof mounting system - Handoko Rusiana Iskandar; Een Taryana; Yuda Bakti Zainal (Universitas Mercu Buana, 2024)
Photovoltaic (PV) systems are designed for both communal and self-installation. PV systems are intended for both communal and standalone installations. Installation is required not only in industry and commerce, but also in the growth of energy potential at Universitas Jenderal Achmad Yani. The focus of this research is rooftop PV modelling and analysis at Universitas Jenderal Achmad Yani. Because the ground mounting system could not be done due to limited land, a rooftop solar power-producing system was created. Data gathering is done as part of unique research that takes into account numerous technological criteria for efficiency. System analysis conducted by modelling and simulation, which will make use of a variety of tools linked to this PV system. Data was gathered from similar studies while accounting for numerous technological variables such as modelling and efficiency. K2Base system was used to model flat roofs with concrete roof types and gable roofs with tile roof types. The mounting type, wind load, truss load, and ballast were all taken into account in the design. This article also calculates PV panel configurations and component capacities. There are many different panels that can be constructed from each model. With a maximum roof area of 837.52 m2, 33 to 350 PV panels may be used. The number of inverters is changed to provide outputs of 10 kW, 25 kW, and 50 kW based on the calculations' findings. With differences in autonomous days, the number of batteries obtained has an average of more than 200 batteries.